Fatigue strength of bilayer yttria-stabilized zirconia after low-temperature degradation - Pereira, Raíssa Monteiro; Belli, Renan; Lohbauer, Ulrich; Hurle, Katrin; Campos, Tiago Moreira Bastos; Thim, Gilmar Patrocínio (Journal of the Mechanical Behavior of Biomedical Materials, 2024)
This study examined the impact of interfacial interactions on bilayer yttria-stabilized zirconia (YSZ) used in dental restorations. In-house bilayer structures of 3YSZ and 5YSZ composition underwent hydrothermal degradation to compare the properties of control and low-temperature degradation (LTD) treated groups. Biaxial flexural strength via piston-on-three-balls, staircase fatigue strength over 106 cycles at 15 Hz, phase characterization and quantification through XRD and Rietveld refinement, and fractography were conducted. Weibull analysis was employed to determine the Weibull modulus and characteristic strength. Results demonstrated an enhancement in the mechanical performance of 3YSZ composition after LTD treatment, whereas the mechanical properties of 5YSZ remained largely unaffected post-degradation. Fractographic analysis revealed that failure originated at the surface tensile location across all specimen groups. These findings offer insights into the mechanical behavior of bilayer zirconia structures and reinforce the significance of hydrothermal treatment in enhancing their performance, particularly in the case of 3Y compositions.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Biaxial flexural strength; Bilayer; Fatigue; Low-temperature degradation; Mechanical properties; Zirconia